2020
DOI: 10.1519/jsc.0000000000002892
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Personal Protective Equipment on Metabolism and Performance During an Occupational Physical Ability Test for Federal Highway Police Officers

Abstract: Marins, EF, Cabistany, L, Farias, CB, Dawes, J, and Del Vecchio, FB. Effects of personal protective equipment on metabolism and performance during an Occupational Physical Ability Test for Federal Highway Police officers. J Strength Cond Res 34(4): 1093–1102, 2020—Federal Highway Police (FHP) officers perform their duties while wearing personal protective equipment (PPE). Given the need for officers to wear PPE, it is important to understand the effects this additional load can have on occupational performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 31 publications
0
30
0
2
Order By: Relevance
“…The age and sex of the police officers in this study were similar to those reported among other specialist teams [ 5 , 12 , 13 , 18 ]. Furthermore, the reported loads carried were greater than non-specialist police officers (~10 kg) [ 9 , 10 , 11 ] and similar to those of other specialist officers (i.e., 20 kg) [ 2 , 12 ]. These findings reiterate the need for strength, power, and aerobic fitness to perform essential job tasks to offset the increased physical burden created by dawning this equipment [ 14 , 23 ].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The age and sex of the police officers in this study were similar to those reported among other specialist teams [ 5 , 12 , 13 , 18 ]. Furthermore, the reported loads carried were greater than non-specialist police officers (~10 kg) [ 9 , 10 , 11 ] and similar to those of other specialist officers (i.e., 20 kg) [ 2 , 12 ]. These findings reiterate the need for strength, power, and aerobic fitness to perform essential job tasks to offset the increased physical burden created by dawning this equipment [ 14 , 23 ].…”
Section: Discussionmentioning
confidence: 95%
“…Police officers are also required to wear personal protective equipment (PPE, such as a ballistic vest) and carry various other equipment items for police work, such as handcuffs, secondary weapons, flashlight, baton, among others [ 9 , 10 ]. These loads, weighing around 10–12 kg, may negatively affect the occupational performance [ 10 , 11 ]. Furthermore, to meet threats beyond the capability of the general police officer, many organizations have created special operations police units (SOPUs).…”
Section: Introductionmentioning
confidence: 99%
“…Part B: Specific Search for Thoracic, Low Back, Sacrum and Coccyx Problems S36 S29 OR S30 OR S31 OR S32 OR S33 OR S34 OR S35 S35 "lumbago" S34 backache OR "back ache" S33 lumb* W3 pain S32 back pain S31 (MH "Low Back Pain") S30 (MH "Back Pain + ") S29 "dorsalgia" Appendix B. 4 Title, abstract, subject field: dor lombar AND tratamento AND (policiais OR policia OR bombeiro OR militar OR "forças armadas" OR aeronáutica OR marinha); limit to type of study: clinical trials, guideline, systematic reviews, cohort, health economic evaluation, health technology assessment, overview (all options present except case studies) Appendix B.8. PubMed (treatment AND (back pain OR backache Or lumbar pain OR lumbago OR dorsalgia OR sciatica) AND (emergency responders OR military personnel OR police OR firefighter OR navy OR naval OR "armed forces" OR "special forces" OR sheriff OR "patrol officer" OR "tactical athlete"OR "law…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…Given the nature of threat to themselves, and to the need to perform these tasks and duties effectively, tactical personnel wear and carry various items of equipment. These items can include, but are not limited to, weapons, communications equipment, body armor, self-contained breathing apparatus, food, and nutrition [1, 3,4]. The weight of this equipment often equates to approximately 10 kg of load for general duties police [4], increasing to over 40 kg if these police are specialists [5], around 20 kg for firefighters [3], and over 45 kg for military personnel [6].…”
Section: Introductionmentioning
confidence: 99%
“…In the line of duty, officers may be required to lift and move heavy objects, pursue and apprehend a suspect, perform hand-tohand combat, jump and climb over fences and barriers, and lift or push heavy objects [2,11,28]. Furthermore, these tasks must be performed while wearing personal protective equipment (PPE) that can weigh approximately 10 kg [4,17,21]. This additional load increases the physical burden placed on the officer and has been shown to negatively impact physical performance [15,17,26].…”
Section: Introductionmentioning
confidence: 99%